2009
DOI: 10.1193/1.3155405
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance of Sacrificial Exterior Shear Keys in Bridge Abutments

Abstract: Performance evaluation of sacrificial exterior shear keys in bridge abutments under simulated seismic loading was conducted in terms of damage levels that were observed during testing. These experiments provided results that were used to make realistic assumptions on the load-deformation response of as-built sacrificial exterior shear keys as well as their peak and post-peak performance under cyclic loads. Experimental results were subsequently used to develop a two-spring component hysteretic model for modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(28 citation statements)
references
References 9 publications
0
27
0
1
Order By: Relevance
“…Ramanathan 7 indicated that these bridge types occupy more than 40% of the California box-girder bridge inventory. The response of the abutment piles is simulated using a trilinear material model presented in Mangalathu et al 11 Exterior shear keys are simulated following the backbone curve of experimental results by Silva et al 31 The foundations are modeled using linear translational and rotational springs. Decks are modeled using linear elements and are connected to columns with rigid links.…”
Section: Numerical Modeling Of Selected Bridges Uncertainties Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramanathan 7 indicated that these bridge types occupy more than 40% of the California box-girder bridge inventory. The response of the abutment piles is simulated using a trilinear material model presented in Mangalathu et al 11 Exterior shear keys are simulated following the backbone curve of experimental results by Silva et al 31 The foundations are modeled using linear translational and rotational springs. Decks are modeled using linear elements and are connected to columns with rigid links.…”
Section: Numerical Modeling Of Selected Bridges Uncertainties Andmentioning
confidence: 99%
“…The hyperbolic soil model proposed by Shamsabadi et al 30 is used to simulate the passive response of the abutment. The response of the abutment piles is simulated using a trilinear material model presented in Mangalathu et al 11 Exterior shear keys are simulated following the backbone curve of experimental results by Silva et al 31 The foundations are modeled using linear translational and rotational springs. The various components previously described are combined to generate the bridge system model for seismic fragility analysis, and the spring connection for the various components is also shown in Figure 2.…”
Section: Numerical Modeling Of Selected Bridges Uncertainties Andmentioning
confidence: 99%
“…Although a detailed description of the analytical modeling technique for this class of bridges can be found elsewhere [4,5,16], the general approach is presented herein. The shear key model is based on the experimental work of Silva et al [22]. The superstructure is modeled as a spline using elastic beam-column elements as it typically remains elastic during a seismic event, and the transverse deck elements are modeled as rigid elements.…”
Section: Characteristics Modeling Technique and Uncertainties Of Thmentioning
confidence: 99%
“…A frictional response model (elastic-perfectly plastic bilinear material model) is used to capture the behavior of abutments on spread footings. The shear key model is based on the experimental work of Silva et al [22]. The typical configuration of the selected box-girder bridge and associated numerical model of various bridge components are shown in Figure 3.…”
Section: Characteristics Modeling Technique and Uncertainties Of Thmentioning
confidence: 99%
“…sliding shear failure and diagonal shear failure, were identified for exterior shear keys. Silva et al performed experimental and analytical investigations to evaluate the seismic performance of sacrificial interior [13] and exterior [14] shear keys. Rational models of the force and deformation capacity of shear keys as well as their postpeak performance under cyclic loads were proposed based on the experimental data.…”
Section: Introductionmentioning
confidence: 99%